The analysis of the convergence criteria. Empirical perspective in the context of the sustainable character highlight - Cristina Maria Triandafil (Romanian Academy, National Institute for Economic Research, 2011)
This study envisages analyzing the convergence criteria in the context of recent macroeconomic developments, focusing on their sustainability. In order to highlight the sustainability of convergence indicators, the paper includes an analysis of the initial dynamics, both in terms of nominal and real plan, highlighting the need for an integrated approach aiming to capture the junction between the two types of convergence processes. Subsequently, sustainability is revealed through the prism of critical aspects, and through the correlation between economic cycles in the European Union. Study findings and proposals tend to review the set of indicators related to the process of nominal convergence towards the integration of real dimension of this process in order to achieve a striking mix.
Keywords: E20; E60; E61; E52; 330; nominal and real convergence; convergence criteria; sustainability of convergence; economic cycles